Association Of Resistin and Adiponectin Levels with Physiological and Inflammatory Parameters in Women with Rheumatoid Arthritis in Wasit Province, Iraq - Nada Hameed Ajam AL-Badri; Eman H. Al-Fadhili; Nada Hameed Ajam AL-Badri (Jurnal MIPA dan Pembelajarannya, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disease affecting the whole body with the presence of constant inflammation at the joints and increased levels of inflammatory mediators while not maintaining normal metabolic homeostasis. The adipokines, such as resistin and adiponectin, secreted by adipose tissue, have been identified as important modulators of inflammatory and immune responses. Their involvement in the RA pathophysiology is not fully understood, especially in Middle Eastern populations. The aim of this study was to evaluate the levels of resistin and adiponectin in the serum of Iraqi women with RA who live in Wasit Province, Iraq, and determine their correlation with inflammatory biomarkers (CRP, ESR, TNF-α, and IL-6), lipid profile (total cholesterol, triglycerides, HDL-C, and LDL-C), and complete blood count (CBC) parameters (Hb, WBC, platelet count, MCV, MCH, and MCHC). The case-control study was carried out at Al-Kut Teaching Hospital and some private clinical laboratories in Al-Kut city, which comprised 60 women with RA (mean age 42.3 ± 8.7 years) and 30 healthy female controls (mean age 40.1 ± 7.9 years). The levels of serum resistin and serum adiponectin were measured using ELISA. Standard laboratory procedures were used to measure inflammatory markers, lipid profiles, and CBC. The Disease Activity Score-28 (DAS28) was used to measure disease activity. Serum resistin was significantly elevated in RA patients (18.6 ± 5.3 ng/mL) compared to controls (7.2 ± 2.1 ng/mL; p<0.001), while adiponectin was significantly reduced (8.4 ± 3.7 vs. 15.9 ± 4.2 μg/mL; p<0.001). Resistin correlated positively with CRP (r=+0.74), ESR (r=+0.68), TNF-α (r=+0.71), IL-6 (r=+0.66), and DAS28 (r=+0.69). Adiponectin inversely correlated with the same parameters. Dyslipidemia (increased LDL-C, triglycerides, decreased HDL-C) and hematological abnormalities were noted in RA patients. Resistin and adiponectin are significantly dysregulated in Iraqi women with RA and closely approximate disease activity and systemic inflammatory load. These adipokines could serve as potential complementary markers for disease severity and metabolic complications of RA.